Accessing water processable cyanido bridged chiral heterobimetallic Co(ii)–Fe(iii) one dimensional network. Issue 2 (10th December 2020) - Choudhury, Anup; Pichon, Céline; Sutter, Jean-Pascal; Pamu, Dobbidi; Sarma, Bipul; Mudoi, Prashurya Pritam; Gogoi, Nayanmoni
Abstract : A simple approach to impart water processability in cyanido bridged extended structures are described. A chiral cyanido bridged Co(ii )–Fe(iii ) extended structure is assembled and its water processability is demonstrated. Abstract : A water processable cyanido bridged extended chiral heterobimetallic Co(ii )–Fe(iii ) network is assembled. The unusual water processability of the coordination polymer originates from dangling hydrophilic substituents. The present approach offers a simple route to impart solution processability to cyanido bridged molecular magnetic materials.